Boosting students’ motivation to read in Japanese using reading journals - Noto, Misato; Ito, Michiru (International Journal of Human Culture Studies, 2020)
Reading skill plays an integral role in furthering one's Japanese learning. To foster students' motivation to read, the effects of extensive reading using journal entries have been examined in past studies. This paper examines the relationship between reading journals and students' motivation to read, through a 5-week period reading project. Participants were given multiple short reading materials for Japanese learners and tasked to take notes of their learning outcomes in detail. Data from journal entries and surveys before and after the project were analyzed to observe any internal changes participants experienced. The pre-study survey illustrated mixed feelings towards reading in Japanese: while the majority expressed positive attitudes towards reading in Japanese, their level of confidence in reading in Japanese was not high. Participants identified limited grammatical and Kanji knowledge as reasons for their low confidence. The 5-week reading project gave participants an opportunity to read all on their own, using contexts and illustrations as clues. The post-study survey showed that the majority of the participants enjoyed being part of the project, and now feel motivated to continue reading in Japanese, despite still facing difficulties with Kanji. Their confidence level saw an overall increase.